Molecular Epidemiological Analysis of ST11-K64 Extensively Drug-Resistant Klebsiella pneumoniae Infections Outbreak in Intensive Care and Neurosurgery Units Based on Whole-Genome Sequencing - Xiong, Liuxin; Su, Lebin; Tan, Hanqing; Zhao, Wansha; Li, Shuying; Zhu, Yingmei; Lu, Limiao; Huang, Zhiwei; Li, Baisheng (Frontiers in Microbiology, 2021)
Klebsiella pneumoniae (KP) is the primary causative bacteria for nosocomial infections and hospital outbreaks. In particular, Extensively Drug-Resistant Klebsiella pneumoniae (XDRKp) causes severe clinical infections in hospitalized patients. This study used the Whole Genome Sequencing (WGS) technology to examine the ST11-K64 XDRKp patient and environmental strains that broke out in the intensive care unit (ICU) and neurosurgery unit. WGS showed that this strain had genomes related to biogenesis (including Type 1 & 3 fimbriae, Type IV pili biosynthesis, RcsAB, type VI secretion system (T6SS)) and multiple drug-resistance (including β-lactamase and aminoglycoside antibiotic resistance). Evolutionary analysis based on core Single Nucleotide Polymorphism (SNP) demonstrated that the strain first appeared in the neurosurgery unit, and there were two transmission chains in this outbreak. Analysis of the feedback results showed that the hospital immediately replaced all the beds and mattresses in the neurosurgery unit and the ICU. Besides, it was required that the physiotherapists disinfect the hands and instruments of each patient after physical therapy and before the subsequent case treatment. They also implemented more stringent isolation and disinfection measures for the infected individuals. Notably, no new cases were reported after implementing these strategies. In summary, WGS has solved the shortcomings of traditional molecular typing technologies (including Pulsed-Field Gel Electrophoresis (PFGE), Multilocus Sequence Typing (MLST), and Multiple Locus Variable-number tandem repeat Analysis (MLVA)) in investigating the outbreak of bacterial infectious diseases and molecular epidemiology. These results provide reliable evidence for inferring the transmission chain of the outbreak and formulating accurate technical support towards preventing and controlling infectious diseases.